Epsilon, a cluster scheduler for Kubernetes clusters - Neo, Alex Jing Hui (Nanyang Technological University, 2021)
The adoption of shared computer clusters for executing high-performance computing workloads has allowed many organizations with limited financial capabilities to access computing power that otherwise might be too costly for them to build. However, to support these heterogeneous workloads, cluster schedulers are getting increasingly complex to develop and maintain as features are added based on different workload requirements.